Detection of immunoglobulins G and A on the cell membrane of hepatocytes from patients with alcoholic liver disease. Issue 5 (May 1983) - Trevisan, A; Cavigli, R; Meliconi, R; Stefanini, G F; Zotti, S; Rugge, M; Noventa, F; Betterle, C; Realdi, G
Abstract : The presence of immunoglobulins (Ig) G, A, and M and of complement fractions (C3-C4) on the liver cell surface was investigated by direct immunofluorescence in 40 patients with alcoholic liver disease. IgG was detected on the liver cell membrane with a linear staining pattern in 29 patients. The percentage of IgG-positive hepatocytes correlated with transaminase activities, independently of the histological findings. IgA was demonstrable with a coarse granular staining pattern in 11 of the 14 cases with established cirrhosis. The finding of IgG bound to the hepatocyte surface in patients with alcohol-induced liver damage suggests that alcohol could be responsible for antigenic modifications of hepatocyte membrane with consequent triggering of a humoral immune response.